The effect of increased frequency of hemodialysis on serum cystatin C and β2‐microglobulin concentrations: A secondary analysis of the frequent hemodialysis network (FHN) trial. Issue 3 (12th March 2019) - Huang, Shih‐Han S.; Kaysen, George A.; Levin, Nathan W.; Kliger, Alan S.; Beck, Gerald J.; Rocco, Michael V.; Filler, Guido; Lindsay, Robert M.
Abstract: Introduction : Small molecular weight toxin clearance is the main method of assessment of hemodialysis efficiency. Middle molecules including cystatin C (CysC) and Beta‐2 microglobulin (β2‐M) are understudied. We hypothesized that lowering of predialysis CysC and β2‐M serum concentrations would be affected by switching to more frequent hemodialysis. Methods : Predialysis CysC and β2‐M serum concentrations were measured from serum samples of the Frequent Hemodialysis Network (FHN) Daily and Nocturnal Trials. The differences between predialysis concentrations at baseline (while on conventional thrice weekly dialysis) and those after 12‐months of study (on more frequent dialysis) were compared separately by trial (Nocturnal, Daily). We tested the associations between predialysis serum CysC and β2‐M concentrations and outcomes. Findings : Forty‐nine percent and 52% of the patients from the FHN Daily and Nocturnal Trials respectively were included in this ancillary study. Predialysis serum CysC concentrations remained unchanged after intensifying hemodialysis dose by either modality. There was significant lowering of the serum β2‐M concentrations in the frequent Daily Trial hemodialysis group at 12 months in all patients and in patients without residual renal function at baseline (−3.8 ± 12.62 μg/mL, P = 0.004; −5.9 ± 12.99 μg/mL, P = 0.02, respectively). There were no significant differences between the baseline and the 12‐months predialysis β2‐M serum concentrations in the two control groups (Daily 3× and Nocturnal 3× groups). No association between the changes in the two biomarkers between baseline and 12‐months and in changes in left ventricular mass, physical‐health composite scores, hospitalization rate, and death were found. The numbers of hospitalizations and deaths were small. Discussion : β2‐M may be a better biomarker of dialysis dose than CysC. Reduction in the concentration of potentially toxic long‐lived proteins of the size of β‐2M is one potential long‐term benefit of more intensive dialysis that may be explored.